Influence of Different Types of Phyllostachys pubescens (Poales: Poaceae) Leaves on Population Parameters of Pantana phyllostachysae (Lepidoptera: Lymantriidae) and Parasitic Effects of Beauveria bassiana (Moniliales: Moniliaceae). Issue 1 (5th April 2015) - Su, Jun; Zhang, Fei-Ping; Huang, Wen-Ling; Chen, De-Lan; Chen, Shun-Li
Abstract : We found that Pantana phyllostachysae, a dangerous pest of moso bamboo ( Phyllostachys pubescens ), showed differences in growth and development after feeding on diverse types of moso bamboo leaves. The mortality rate of Pa. phyllostachysae due to Beauveria bassiana, an entomopathogenic fungus, was also affected by the varied larval diet. Larval and pupal developmental duration of Pa. phyllostachysae was longer when feeding on "off-year" bamboo leaves. Pupal weight and adult fertility were higher when feeding on "on-year" bamboo leaves. Mortality due to B. bassiana was significantly lower in larvae fed on on-year bamboo leaves than in larvae fed on off-year bamboo leaves. Larvae fed on new bamboo leaves had a shorter development period and higher survival rate than those fed on off-year bamboo leaves. However, mixed feed (mixture of new, on-year, and off-year bamboo leaves) decreased the egg production of Pa. phyllostachysae. After infection by the second generation of B. bassiana, the survival time of Pa. phyllostachysae fed on mixed feed increased significantly compared with the first generation. We also fed Pa. phyllostachysae different proportion of new bamboo leaves in mixed feed to simulate natural conditions. We found that increasing the proportion of new bamboo leaves in the food promoted pupal development and increased egg production; it also increased the resistance of larvae to the first generation of B. bassiana . The pathogenicity of the second generation of B. bassiana declined in all mixed feed treatments.